Hospital consumption of direct oral anticoagulants in regions of the Russian Federation in 2017–2022 - A. V. Matveev; S. V. Glagolev; K. N. Koryanova; D. A. Sychev (Фармация и фармакология (Пятигорск), 2024)
The aim of the study was to investigate the dynamics of inpatient consumption of direct oral anticoagulants in different regions of the Russian Federation for the period from 2017 to 2022.Materials and methods. This study is a non-interventional, retrospective analysis of the electronic database records of Cursor Marketing LLC (Russia) about the announced by medical organizations and executed contracts for the purchase of direct oral anticoagulants (DOACs). The сonsumption was calculated on the basis of a DDD (defined-daily-dose) and estimated DDDTID (defined-daily-dose/1000-inhabitants/day) for each DOACs: rivaroxaban, dabigatran and apixaban. The Rosstat database available on its official website were used as a source of inhabitants data for the Russian regions.Results. A total of 57 866 records were entered into the analyzed databases of Cursor Marketing LLC (Russia) from 2017 to 2022, 47.38% of which indicated rivaroxaban as the drug being procured, 26.51% indicated dabigatran, and 26.11% indicated apixaban. Edoxaban was not procured by healthcare organizations. During the period investigated, there was an increase in the consumption of all DOACs studied, with a higher increase for apixaban (by an average of 284.6% per year), then rivaroxaban (by 144.8% per year) and, to a lesser extent, dabigatran (by 92.5% per year). The analysis of DOACs consumption in general showed that compared to 2017, the need for these drugs in medical organizations in 2022 increased by 18 times. The Urals Federal District consistently exceeds the national average in terms of DDTID consumption. Noteworthy is the consumption dynamics of the regions of the Central Federal District and the North-Western Federal District, which made it possible to achieve DDDTID values above the national average for 5 out of 6 observation years. The lowest rates of DOACs consumption were observed in the Volga Federal District, which, despite positive growth dynamics, failed to reach the national average values. A high level of consumption (>10 DDDTID) of rivaroxaban was noted for the Arkhangelsk region (2018) and the Nenets Autonomous District (in 2021), dabigatran – only for the Arkhangelsk region (in 2018). Many more regions reached high levels of the apixaban consumption, especially in 2021.Conclusion. Despite a number of limitations, the data on the volume of DOACs procurement can be used in the analysis of the consumption at both regional and national levels. When analyzing the DOACs consumption, the impact of COVID-19 pandemic and pharmacogenetic features of patients in different regions should be taken into account. During the studied period of time, a significant part of the Russian regions achieved a consumption level of rivaroxaban and apixaban, but not dabigatran, exceeding 1 DDDTID.